Casa en Punta Chica (2007)
Material gráfico y memoria descriptiva de la casa en Punta Chica.
Keywords: VILA SEBASTIAN VILA & ASOCIADOS ARQUITECTOS; VILA, MARCELO; SEBASTIÁN, ADRIÁN; VILA, JAVIER; VIVIENDAS UNIFAMILIARES; VIVIENDAS SUBURBANAS; SAN FENANDO; BUENOS AIRES (PROV); ARGENTINA; CONSTRUCCION EN PENDIENTE; CONSTRUCCION; HORMIGON; CERRAMIENTOS; VIDRIO